Effectiveness of Fruit Peels Eco Enzyme in Reducing Total Chromium from Yogyakarta Tanning Industry Waste - Putri, Caecilia Radella Rivika; Jati, Alphonsus Wibowo Nugroho; Yulianti, Lorensia Indah Murwani (Jurnal Biodjati, 2024)
. Leather tanning industry is essential in Indonesia's economic sector, specifically in the export of hides and leather goods. The high production of goods is often accompanied by a large amount of waste disposal, containing elevated levels of chromium which has a negative effect on the environment. To address this problem, eco enzyme containing high carboxyl groups is expected to be an effective solution. Therefore, this study aimed to determine the functional groups in fruit peels eco enzyme and its effectiveness in reducing total chromium content in leather tanning waste. The experimental process included the preparation of eco enzyme formulations, testing functional groups with FTIR, and determining total chromium content using AAS. Furthermore, the characteristics of waste were determined, including such as BOD, pH, temperature, ammonia, TDS, and TSS, followed by incubation of eco enzyme in waste, as well as data analysis with ANOVA and Duncan test. The results showed that eco enzyme formulations contained hydroxyl (O-H) and carboxyl (-COOH) functional groups, carbon-carbon single bonds (C-C), carbon-oxygen single bonds (C-O), carbon-carbon double bonds (C=C), and carbon-hydrogen bonds (C-H). All formulations effectively reduced chromium levels in leather tanning waste to value lower than quality standards. Based on the results, the best formulation was found to be eco enzyme A, which comprised one type of fruit, namely mango peels.